Digital Transformation of English Language Teaching (ELT) at Junior High School Level: A Case Study in Remote Area of West Kalimantan - Nurhayati, Siti; Yuliana, Yohanes Gatot Sutapa; Regina, Regina (LP. Ma'arif Janggan Magetan, 2024)
The development of technology runs very rapidly in this day and age. Indonesian are no exception to the worldwide trend toward greater reliance on digital technologies. And the Sambas community as residents of border areas tend to enter underdeveloped areas in various aspects of life, including in the field of education, especially in English language learning. The weak use of English communication for students living at the border further complicates opportunities to enter the workforce. As a border area with a high intensity of interaction and communication with other countries, it demands mastering English from an early age. The border area should get special attention from the government because the border area is a strategic area from the point of defense and security of a country and as an attraction for trade and tourism. Learning using digital means must absolutely be mastered by teachers as a means of improving English learning in the area. Based on the explanation above, this research reveals the problem that exists in digital English language teaching (ELT) at the junior high school level in border areas. Case study research, which is used in this study, is a qualitative method that aims to reveal issues that are otherwise unseen and to convey stories of problem-solving or situations based on data collected in the field